Pengaruh Lingkungan Kerja dan Kepuasan Kerja Terhadap Motivasi Kerja Karyawan di Edutech Startup dengan Sistem Kerja Fleksibel - Muhammad Multazam; Christian Wiradendi Wolor; Sholikhah Sholikhah (Indo Publishing, 2026)
This study aims to analyze the influence of the work environment and job satisfaction on work motivation in employees at an edutech startup with a flexible work system. The research method used is quantitative with a survey approach. Data were collected through a questionnaire that included positive statements about the work environment and job satisfaction. The data analysis technique used multiple linear regression analysis to examine the relationship between the work environment, job satisfaction, and work motivation. The results of the study indicate that the work environment has a positive and significant influence on work motivation, meaning that the better the work environment, the higher the work motivation. Job satisfaction also has a positive and significant influence, meaning that the higher the job satisfaction, the higher the work motivation. Then, simultaneously, it was found that there was a positive and significant influence of the work environment and job satisfaction on work motivation.